Divided Loyalties? Pushing the Boundaries of Gender and Lay Roles in the Catholic Church, 1534-1829 - McClain, Lisa (Histories of the Sacred and Secular, 1700-2000, 2018)
This book explores changing gender and religious roles for Catholic men and women in the British Isles from Henry VIII's break with the Catholic Church in 1534 to full emancipation in 1829. Filled with richly detailed stories, such as the suppression of Mary Ward's Institute of English Ladies, it explores how Catholics created and tested new understandings of women's and men's roles in family life, ritual, religious leadership, and vocation through engaging personal narratives, letters, trial records, and other rich primary sources. Using an intersectional approach, it crafts a compelling narrative of three centuries of religious and social experimentation, adaptation, and change as traditional religious and gender norms became flexible during a period of crisis. The conclusions shed new light on the Catholic Church's long-term, ongoing process of balancing gendered and religious authority during this period while offering insights into the debates on those topics taking place worldwide today.